Validasi Modul “Cakap” untuk Meningkatkan Keterampilan Sosial Mahasiswa Baru Asal Bali - Ni Made Yanthi Ary Agustini; Budi Andayani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2017)
Having low social skills can make individuals experience difficulty adjusting to a new environment. The purpose of this research is to validate "CAKAP" module to improve social skills. This study used a quantitative approach with the quasi-experimental design of The Untreated Control Group Design with Pretest and Posttest. Social skills scale, observation sheet, and evaluation sheet were administrated to 14 freshmen from Bali who joined in Keluarga Mahasiswa Hindu Dharma (KMHD).  The test results of the content validity of the module using Aiken's V shows a value ranging from 0,734-0,861 for each session which means the module has good content validity. Empirical test results showed that there was a difference gained score between experimental group and control group (z = -2,194, p = 0,026, p <0,05). The results show that the module "CAKAP" is valid to improve social skills on freshmen from Bali.